2011
DOI: 10.1080/1331677x.2011.11517482
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Remittances in Financial Crisis: Empirical Evidence from Macedonia

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…). Moreover, Bucevska () examined the role of remittances in financial crisis using the vector error correction (VEC) model and found that real remittances have a destabilizing effect on the economic growth and do not cushion large fluctuations during economic downturn.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…). Moreover, Bucevska () examined the role of remittances in financial crisis using the vector error correction (VEC) model and found that real remittances have a destabilizing effect on the economic growth and do not cushion large fluctuations during economic downturn.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With respect to Macedonia, studies conducted at household level show that remittances have a positive effect on consumption, poverty reduction, health (especially for females and rural dwellers), and owning businesses (Petreski & Jovanovi c, 2013a, 2016Petreski et al 2014). Moreover, Bucevska (2011) examined the role of remittances in financial crisis using the vector error correction (VEC) model and found that real remittances have a destabilizing effect on the economic growth and do not cushion large fluctuations during economic downturn.…”
Section: Introductionmentioning
confidence: 99%
“…The Romanians working abroad have become, due to their remittances, one of the most important foreign direct investors (in 2017 Remittances were 2.02% of GDP while Foreign Direct Investments were 2.33% of GDP), which are considered a large source of external financing. (Gradi, 2014 andBucevska, 2011). Under those circumstances, there are more and more questions about the way those remittances influence not only the migrants' families that were left behind, but also the economic development of the country.…”
Section: Remittances and The Economic Growthmentioning
confidence: 99%
“…The list of jobs, where labor shortages are persisting, was set by a special Commission and then published on the website of the Central Office of Labor, Social Affairs and Family. It is updated on the annual basis (Bucevska, 2011;Crespo Cuaresma et al, 2014).…”
Section: Recruitment Of Workers From Third Countriesmentioning
confidence: 99%